Viscoelastic effects on the overall responses of Terfenol-D/polymer composites. (1st February 2023) - Lin, Chien-hong; Hung, Yu-Cheng
Highlights: A mathematical framework is developed for modeling viscoelastic behaviors of Terfenol-D/polymer composites. Viscoelastic polymer matrix causes the overall responses of polymer matrix smart composites to be time-dependent. The effects of constituent, connectivity, proportion, and loading rate on the overall viscoelastic behavior are studied. The 1–3 connectivity provides the best magnetostriction but at the cost of the unavoidable hysteretic behavior. Due to viscoelastic polymer, Δ E -effect accompanies hysteresis curves in Terfenol-D polymer matrix composites is shown. Abstract: When polymers combine with Terfenol-D constituents, the resulting composites inherently exhibit time-dependent and magnetoelastic coupling behaviors. Herein, we present a mathematical framework to simulate the effective viscoelastic behaviors of Terfenol-D/polymer composites via an incremental micromechanics analysis that is based on the homogenization technique for periodic composites in conjunction with a time-integration technique that enables the use of a recursive algorithm for fast and easy solution of the convolution integral constitutive law for linear viscoelastic polymers. The representation of the monolithic Terfenol-D material is based on a recently developed nonlinear constitutive equation. The resulting composite constitutive relation that governs the time-dependent behaviors of composites are first verified by experimental data existing in literatures and then implemented to study the viscoelastic responses of a polymeric matrix with embedded Terfenol-D particles, continuous fibers and layers, respectively. The hysteresis loops in magnetostriction and magnetic flux density responses as well as in Δ E -effect of this composite due to cyclic magnetic loadings together with prestresses and environmental temperatures are shown. We find that even though the Terfenol-D does not show viscoelastic behaviors, an overall time-dependent magnetoelastic coupling responses of this composite still occurs, arising from viscoelastic effects in the polymer.